Electron density shift in imidazolium derivatives upon complexation with cucurbit[6]uril - Kolman, Viktor; Marek, Radek; Strelcova, Zora; Kulhanek, Petr; Necas, Marek; Svec, Jan; Sindelar, Vladimir (Chemistry (Weinheim an der Bergstrasse, Germany), 2009)
In this study, we have investigated the supramolecular interaction between series of 1-alkyl-3-methylimidazolium guests with variable alkyl substituent lengths and cucurbit[6]uril (CB6) in the solution and the solid state. Correct interpretation of (1)H NMR spectra was a key issue for determining the binding modes of the complexes in solution. Unusual chemical shifts of some protons in the (1)H NMR spectra were explained by the polarization of the imidazolium aromatic ring upon the complexation with the host. The formation of 1:1 complex between 1-ethyl-3-methylimidazolium and CB6 is in disagreement with previously reported findings describing an inclusion of two guest molecules in the CB6 cavity.
Keywords: Ionic Liquids; Imidazoles; imidazoly; Bridged-Ring Compounds; Models, Molecular; iontové kapaliny; elektrony; molekulární modely; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Electrons; přemostěné cyklické sloučeniny